Potential factors affecting the impact of community reinforcement and family training. Secondary analysis of an RCT - Rikke Hellum; Randi Bilberg; Anna Mejldal; Anette Søgaard Nielsen (BMC, 2024)
Abstract Background In addition to increasing the quality of life among concerned significant others (CSOs), Community Reinforcement and Family training (CRAFT) aim at helping CSOs motivate treatment-refusing identified patients (IPs) into treatment through a positive reinforcement process. The aim of the present study was to investigate if the following factors, measured at baseline, have an influence on IP future treatment engagement (1) Type of relation between CSO and the IP (2) The amount of time the CSO spend with the IP (3) if the IP knows that the CSOs seeks help, and (4) The CSO's own alcohol use. Methods A secondary analysis from the Danish CRAFT study. CSOs completed a self-administered questionnaire at baseline, after three months, and six months. To investigate the relationship between the four variables and treatment engagement, logistic regression was used. Results CSO's relation to the IP, the frequency of contact between the CSO and the IP, and the CSO's AUDIT score at the time of the baseline interview were not associated with the IP's treatment engagement. If CSO at baseline had informed the IP that the CSO participated in CRAFT, odds for IP treatment engagement were significantly higher (adjusted OR [(CI)] = 2.29 [1.13; 4.63] (p < 0.05), relative to if IP not being informed. Conclusions CRAFT has a higher impact on the likelihood for treatment seeking, if the CSOs inform the IP about his or her own help seeking in order to change the situation. The underlying mechanism behind this is needs further investigations.